Respuesta :
The correct answer is
[tex]A) x^2 - 6x + 9[/tex]
In fact, this is a trinomial of the form [tex]ax^2-bx+c[/tex], whose solutions are given by
[tex]x_{1,2}= \frac{-b\pm \sqrt{b^2 -4ac} }{2a}[/tex]
Using this formula for the trinomial of the problem, we find:
[tex]x1,2= \frac{6 \pm \sqrt{6^2-4\cdot 1\cdot 9}}{2} =3[/tex]
we see that this trinomial has two coincident solutions (x=3 with multiplicity 2). This means that it can be rewritten as a perfect square, in the following form:
[tex](x-3)^2[/tex]
[tex]A) x^2 - 6x + 9[/tex]
In fact, this is a trinomial of the form [tex]ax^2-bx+c[/tex], whose solutions are given by
[tex]x_{1,2}= \frac{-b\pm \sqrt{b^2 -4ac} }{2a}[/tex]
Using this formula for the trinomial of the problem, we find:
[tex]x1,2= \frac{6 \pm \sqrt{6^2-4\cdot 1\cdot 9}}{2} =3[/tex]
we see that this trinomial has two coincident solutions (x=3 with multiplicity 2). This means that it can be rewritten as a perfect square, in the following form:
[tex](x-3)^2[/tex]
Answer:
a. x2 – 6x + 9
Step-by-step explanation:
In order to solve this you just have to try and factorize the options and the result should be two exact binomials. Remember that the formula for perfect square trinomial is:
[tex]a^{2} +2ab+b^{2} =(a+b)(a+b)[/tex]
So we only have to factorize x2-6x+9=
As you can see, a is equal to X, and b equals 3:
(x-3)(x-3)=x2-6x+9
SO this is a perfect square trinomial.